Business Continuity for Global Enterprises: The Importance of Protecting and Managing Information Assets - Ruettgers, Mike (Tufts Archival Research Center, 2005)
Volume 27, Issue 2. Summer/Fall Key business continuity lessons from September 11 point to the need for effective planning as well as responsible corporate governance.